2014
DOI: 10.2147/ndt.s70818
|View full text |Cite
|
Sign up to set email alerts
|

Parental bonding and attitudes toward suicide among medical college students in Japan

Abstract: BackgroundSuicide is a grave public health issue that is responsible for a high mortality rate among individuals aged 15–44 years. Attitudes toward suicide among medical staff members have been associated with appropriate therapeutic responses to suicidal individuals. The aim of this study was to examine the effects of parental rearing on attitudes toward suicide among Japanese medical college students.MethodsWe examined the association between parental bonding and attitudes toward suicide in 160 medical colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This study suggests that college students who have suicidal thoughts are more likely to have been subjected to improper parenting styles, including being scolded and physically punished by parents; to have felt learning pressure from parents; and to have had a poor relationship with their parents. Other surveys have also concluded that suicidal ideators are subjected to poor parenting methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that college students who have suicidal thoughts are more likely to have been subjected to improper parenting styles, including being scolded and physically punished by parents; to have felt learning pressure from parents; and to have had a poor relationship with their parents. Other surveys have also concluded that suicidal ideators are subjected to poor parenting methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents burden their students with the pressure to learn. Studies in other countries have shown that suicidal ideation is associated with parenting methods [ 19 ]. It may be that improper parenting increases the risk of suicidal ideation in children.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first to analyze the association between parenting attitudes and attitudes toward suicide in the adolescent population and to explore how this association affects suicidal ideation. Although there has been one study on the association between adult attitudes toward suicide and parents’ parenting attitudes, the sample size was small and only included students at a medical school in Japan [ 30 ], and the impact of this association on suicidal ideation was not examined. Our study has the advantage of a larger sample size and advanced investigation of the mediating effects of ATTS between parenting style and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was conducted to determine the relationship between parental bonding and attitudes toward suicide in medical students in Japan. The researchers concluded that high levels of maternal care ensured reduced suicidal ideation [17]. In Iran, results of a cross-sectional study on university students showed that the students who experienced a less caring parental bonding style, had signi cantly higher psychological symptoms, particularly depression, anxiety, and paranoia [18].…”
Section: Introductionmentioning
confidence: 99%